دور الدبلوماسية الجزائرية في تسوية النزاعات اإلفريقية -ليبيا ومالي أنموذجا- - قوادرية علي (المسيلة, 2023)
تعالج هذه الدراسة دور الدبلوماسية الجزائرية في تسوية بعض نزاعات دول الجوار في ليبيا ومالي بدء بالإشادة بنشاطات الدبلوماسية الجزائرية أثناء الثورة التحريرية وبعد الاستقلال،والتطرق لأهم محددات ومبادئ الدبلوماسية الجزائرية كعدم التدخل في الشؤون الداخلية للدول وتسوية النزاعات بالطرق السلمية ، والاهتمام بدراسة أداء الدبلوماسية من خلال مبادرات التسوية السلمية للنزاع الليبي والمالي،وأهم تداعياتهما على الأمن الجزائري ، والتركيز على المقاربة الجزائرية لتسوية الأزمتان بالتأكيد على الحل السلمي وجمع الأطراف للحوار بعيدا عن التدخل الخارجي،كما تم التطرق لأهم التحديات الداخلية والخارجية التي تواجه الأمن الجزائري كالتحدي السياسي، والأمني، والمجتمعي،وتدخل الأطراف الخارجية، والعمل على ترسيخ مقاربة الأمن والتنمية كمحور لتحقيق الأمن والاستقرار في دول الجوار الإقليمي. الكلمات المفتاحية: الدبلوماسية، الوساطة، التسوية، النزاع، الأزمة. Abstract This study deals with the role of Algerian diplomacy in settling some disputes of neighboring countries in Libya and Mali, starting with praising the activities of Algerian diplomacy during the liberation revolution and after independence, and addressing the most important determinants and principles of Algerian diplomacy such as non-interference in the internal affairs of countries and the settlement of disputes by peaceful means, and interest in studying the performance of diplomacy through Initiatives for the peaceful settlement of the Libyan and financial conflict, and their most important repercussions on Algerian security, focusing on the Algerian approach to resolving the two crises by emphasizing a peaceful solution and bringing the parties together for dialogue away from external interference. External parties, and work to consolidate the security and development approach as a focus for achieving security and stability in the regional neighboring countries. Keywords:diplomacy, Medition, Settlement, dispute, Crisis.
Keywords: الوساطة، التسوية، النزاع، الأزمة.